2013
DOI: 10.1128/cvi.00145-13
|View full text |Cite
|
Sign up to set email alerts
|

A Live Attenuated Human Metapneumovirus Vaccine Strain Provides Complete Protection against Homologous Viral Infection and Cross-Protection against Heterologous Viral Infection in BALB/c Mice

Abstract: A live attenuated vaccine candidate strain (M2) of human metapneumovirus (hMPV) was generated by removing the N-linked carbohydrate at amino acid 172 in the fusion (F) protein. Previously, replication of M2 in mouse lungs could be detected by molecular assays but not by viral titration. In the present study, the protective effects of M2 against infection by homologous or heterologous viruses were evaluated in BALB/c mice. Immunization with M2 produced a high titer of serum virus-neutralizing antibodies in BALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This vaccine was found to give complete protection against homologous virus challenge and some protection against heterologous viral challenge, even with a challenge at 56 days post-inoculation. 102 All these findings suggest that before an effective vaccine against hMPV can be developed, more detailed knowledge of the molecular pathogenesis of hMPV is required.…”
Section: Treatment and Control Strategiesmentioning
confidence: 99%
“…This vaccine was found to give complete protection against homologous virus challenge and some protection against heterologous viral challenge, even with a challenge at 56 days post-inoculation. 102 All these findings suggest that before an effective vaccine against hMPV can be developed, more detailed knowledge of the molecular pathogenesis of hMPV is required.…”
Section: Treatment and Control Strategiesmentioning
confidence: 99%
“…Several vaccine strategies against HMPV have been explored in animal models, including live attenuated, subunit protein, formalin-inactivated, and CD8 ϩ T cell (T CD8 ) epitope vaccines (9,(13)(14)(15)(16)(17). However, live attenuated viruses are contraindicated in immunocompromised patients.…”
mentioning
confidence: 99%
“…A prior report by Alvarez et al (18) suggested that NK cells had a role in limiting HMPV replication, as NK cell-depleted BALB/c mice had higher lung titers; however, that model described biphasic viral kinetics and long-term persistence not confirmed by others (13,(19)(20)(21)(22)(23)(24)(25)(26). The discrepancy could be due to different mouse and virus strains or different depletion antibodies or protocols.…”
mentioning
confidence: 55%